2014
DOI: 10.1159/000364915
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife Radiosurgery of Paracentral Epilepsy

Abstract: Background: In pharmacoresistant focal epilepsies involving the central region, risk of motor deficit generally contraindicates cortical resection. Gamma knife radiosurgery (GK) is an established treatment for mesial temporal epilepsy and epilepsy associated with hypothalamic hamartoma. Objectives: To explore the safety profile and efficacy of GK in motor cortex epilepsies. Methods: Four patients (18-31 years) with intractable focal sensorimotor epilepsy seizures arising from the paracentral lobule, demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
(41 reference statements)
0
5
0
1
Order By: Relevance
“…GK is an effective treatment of hypothalamic hamartoma. [15][16][17][18] Up to now, however, few data were available on the potential endocrine side effects of such treatment. To our knowledge, only one study reported the endocrine outcome of patients treated by GK for hypothalamic hamartoma: Abla et al 19 reported no pituitary deficiency in 15 patients followed for 18-81 months, but did note the occurrence of transient poikilothermia in one, weight gain in 2, and anxiety and depression in 2 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GK is an effective treatment of hypothalamic hamartoma. [15][16][17][18] Up to now, however, few data were available on the potential endocrine side effects of such treatment. To our knowledge, only one study reported the endocrine outcome of patients treated by GK for hypothalamic hamartoma: Abla et al 19 reported no pituitary deficiency in 15 patients followed for 18-81 months, but did note the occurrence of transient poikilothermia in one, weight gain in 2, and anxiety and depression in 2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…GK is an effective treatment of hypothalamic hamartoma . Up to now, however, few data were available on the potential endocrine side effects of such treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Especially relevant to cardiac SBRT is stereotactic radiosurgery (SRS) for temporal epilepsy, which involves the use of video-scalp-electroencephalogram and MRI to map seizure substrate. [20][21][22] This technique mirrors the multimodality approach to ablation that has become standard in the EP field. 21,22 Taken together, EP and radiation oncology share a history of multimodal therapy development which can naturally facilitate cross-disciplinary integration of diagnostic techniques heretofore specific to each field for cardiac SBRT.…”
Section: Historical Context To Cardiac Sbrtmentioning
confidence: 99%
“…[20][21][22] This technique mirrors the multimodality approach to ablation that has become standard in the EP field. 21,22 Taken together, EP and radiation oncology share a history of multimodal therapy development which can naturally facilitate cross-disciplinary integration of diagnostic techniques heretofore specific to each field for cardiac SBRT.…”
Section: Historical Context To Cardiac Sbrtmentioning
confidence: 99%
“…Antikonvulsiva sollten daher auch nach mehrjähriger Anfallsfreiheit weiter gegeben werden. Alternativen zur "klassischen" epilepsiechirurgischen Operation wie Gamma-Knife-Bestrahlung und Hochfrequenz-Thermokoagulation sind zurzeit Gegenstand der Forschung und können möglicherweise bei einem Teil der Patienten in Zukunft sinnvoll sein [63,64].…”
Section: Frontallappenepilepsien ▼unclassified